Synthesis method and application of metal element modified molybdenum-based sulfur-phosphorus compound catalyst with high C2 + alcohol selectivity

The synthesis of metal element modified molybdenum-based thiophosphate complex catalysts was solved by the low-temperature plasma method, and the problems of high selectivity and low reactivity in the existing C2+ alcohol catalytic system were achieved, and the effects of high selectivity and high reactivity of C2+ alcohol were achieved.

CN119746894APending Publication Date: 2025-04-04INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411918811.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing C2+ alcohol catalytic system has problems such as high selectivity of methanol, low reactivity, and widening of alcohol distribution, which is difficult to meet the needs of efficient C2+ synthesis catalysts.

Method used

The metal element modified molybdenum-based thiophosphate complex catalyst was synthesized by low-temperature plasma method. By controlling the mass of sulfur and phosphorus elements and the proportion of molybdenum elements, the structure and performance of the catalyst were adjusted to form a catalyst with high C2+ alcohol selectivity.

Benefits of technology

It has achieved high catalytic CO conversion rate and high C2+ alcohol selectivity, and the CO conversion rate and C2+ alcohol selection performance of some catalysts reach more than 90%. The synthesis process is simple and convenient to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746894A_ABST
    Figure CN119746894A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst synthesis, and relates to a synthesis method of a metal element modified molybdenum-based sulfur-phosphorus compound catalyst with high C2 + alcohol selectivity, which comprises the following steps: uniformly mixing a modified metal salt and a molybdenum compound to obtain a mixture A, in which the molar ratio of the modified metal to molybdenum is 0.01-50; the phosphorus elementary substance powder, the sulfur elementary substance powder and the mixture A are evenly mixed to obtain a mixture B, in the mixture B, the molar ratio of phosphorus to sulfur is 0.1-10, and the molar ratio of phosphorus to molybdenum is 0.05-40; and placing the mixture B in a reaction tube of a plasma reactor, introducing discharge gas to complete ionization of the gas to form plasma, and reacting for 5-300 minutes to finally prepare the metal element modified molybdenum-based sulfur-phosphorus compound catalyst with high C2 + alcohol selectivity. The invention also relates to application of the catalyst prepared by the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst synthesis, and in particular relates to a synthesis method and application of a metal element modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity. Technical Background

[0002] The development of one-step synthesis gas (H2 and CO mixture) to produce C2+ alcohols is an important strategic means for my country to achieve efficient and clean utilization of coal in the face of new energy situations. As a bulk chemical, C2+ alcohols have a wide range of uses and can be used as basic chemical raw materials, oil additives, liquid fuels, etc. Therefore, in the one-step synthesis gas to produce C2+ alcohols technology, the synthesis of high-performance catalysts with high C2+ alcohol product selectivity is the core of the current promotion of the further development of this technology.

[0003] At present, there are four main types of catalysts for the one-step preparation of C2+ alcohols from syngas: modified Cu-based methanol catalysts, modified Fischer-Tropsch synthesis (Fe, Co, Ni-based) catalysts, noble metal Rh-based catalysts, and MoS2-based catalysts. The modified Cu-based methanol catalyst has good selectivity for total alcohols, but the proportion of methanol in the product is high, and the active phase Cu is easy to sinter at high temperatures; although the proportion of C2+ alcohols in the total alcohols of the modified Fischer-Tropsch synthesis (Fe, Co, Ni-based) catalyst is high, the strong carbon chain growth ability of the Fischer-Tropsch element improves the selectivity of high-carbon alcohols; the advantage of the noble metal Rh-based catalyst is the high ethanol content, but there are many acid and ester by-products, and the high price also limits its application; the MoS2-based catalyst can be applied to hydrogen-poor syngas, and it is not easy to deposit carbon, has strong resistance to sulfur poisoning, and its good stability also prolongs the reaction cycle, but its alcohol product has a high methanol content and low reaction activity. Although the use of Fischer-Tropsch element modification can significantly reduce the methanol selectivity, it inevitably brings about the problem of wide distribution of alcohols. In summary, the existing domestic and foreign C2+ alcohol catalytic systems have the above-mentioned shortcomings, and it is extremely urgent to develop new and efficient C2+ synthesis catalysts. Summary of the invention

[0004] The purpose of the present invention is to provide a method for synthesizing a metal element modified molybdenum-based sulfur-phosphorus complex catalyst with high C2+ alcohol selectivity. The method has a simple synthesis route and is easy to operate. The synthesized metal element modified molybdenum-based sulfur-phosphorus complex catalyst has the advantages of small particle size and high active phase dispersion, and has high catalytic CO conversion rate and high C2+ alcohol selectivity.

[0005] The basic synthesis principle of the metal element modified molybdenum-based sulfur-phosphorus complex catalyst with high selectivity for C2+ alcohols of the present invention is: the plasma is rich in a large number of highly active species such as electrons, ions, excited atoms, molecules and free radicals. The energy contained in these high-energy particles is about several to tens of electron volts (eV), which is enough to provide the activation energy required for chemical reactions and is called the fourth form of matter. In the plasma, high-energy particles bombard a mixture of sulfur and phosphorus, uniformly forming an excited sulfur-phosphorus gaseous plasma with very active chemical properties, and acting in situ on metal salts, molybdenum salts or molybdenum oxide precursors, avoiding high-temperature treatment under mild conditions, and forming a metal element modified molybdenum-based sulfur-phosphorus complex catalyst.

[0006] A method for synthesizing a metal element modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity is carried out according to the following steps

[0007] Step 1, preparing a mixture A, mixing the modified metal salt and the molybdenum compound uniformly to obtain a mixture A, wherein the molar ratio of the modified metal to molybdenum in the mixture A is 0.01-50;

[0008] Step 2, preparing a mixture B, mixing phosphorus powder, sulfur powder and mixture A uniformly to obtain a mixture B, wherein the molar ratio of phosphorus to sulfur is 0.1-10, and the molar ratio of phosphorus to molybdenum is 0.05-40;

[0009] Step 3: Place the mixture B in a reaction tube of a plasma reactor (and in a cavity formed by a high-voltage electrode), introduce discharge gas at a flow rate of 5-2000 ml / min, output a voltage of 1000-25000V, and discharge a high voltage of 1-40kHz to ionize the gas to form plasma, react for 5-300 minutes, and finally obtain a metal element modified molybdenum-based sulfur-phosphorus complex catalyst with high C2+ alcohol selectivity.

[0010] The modified metal salt is one of nickel sulfate, nickel nitrate, nickel chloride, sodium sulfate, sodium nitrate, sodium chloride, calcium sulfate, calcium nitrate, calcium chloride, barium sulfate, barium nitrate, barium chloride, niobium sulfate, niobium nitrate, niobium chloride, rhodium sulfate, rhodium nitrate, rhodium chloride, palladium sulfate, palladium nitrate, palladium chloride, platinum sulfate, platinum nitrate, platinum chloride, cadmium sulfate, cadmium nitrate, cadmium chloride, gallium sulfate, gallium nitrate, gallium chloride, lanthanum sulfate, lanthanum nitrate, lanthanum chloride, zirconium sulfate, zirconium nitrate, zirconium chloride, cerium sulfate, cerium nitrate, cerium chloride, zinc sulfate, zinc nitrate, zinc chloride, manganese sulfate, manganese nitrate, manganese chloride, copper sulfate, copper nitrate, copper chloride, ferric sulfate, ferric nitrate, ferric chloride, chromium sulfate, chromium nitrate, chromium chloride, ammonium tungstate, potassium sulfate, potassium nitrate or potassium chloride.

[0011] The molybdenum compound is one of carbonyl molybdenum, ammonium molybdate, molybdenum dioxide or molybdenum trioxide.

[0012] The phosphorus element is one of white phosphorus, red phosphorus, black phosphorus or purple phosphorus.

[0013] The reaction tube is one of a corundum tube, a glass tube or a ceramic tube.

[0014] The discharge gas is one of air, oxygen, H2, N2, He or Ar.

[0015] A metal element modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity is used. The metal element modified molybdenum-based sulfur-phosphorus composite catalyst prepared by 40-60 mesh is evenly mixed with quartz sand, and then loaded into a high-temperature and high-pressure fixed bed reactor; the hydrogen-carbon ratio (H2 / CO) of the synthesis gas is controlled by a mass flow meter to be 0.2-10, and the volume space velocity is 300-15000h -1 The reaction conditions are reaction temperature 200-400 degrees, reaction pressure 2.5-12MPa, and reaction time 5-24 hours.

[0016] Effects and benefits of the present invention: The present invention adopts a low-temperature plasma method to avoid the high-temperature preparation process of the catalyst, and the synthesis time is short and the operation is convenient. It realizes the precise adjustment of the relative content of sulfur and phosphorus in the molybdenum-based sulfur-phosphorus complex by controlling the mass of sulfur and phosphorus at low temperature under normal temperature and pressure, and at the same time adjusts the ratio of molybdenum element and modified metal element to finally synthesize a molybdenum-based sulfur-phosphorus complex catalyst with a regular structure, high dispersion and nano-level uniform particles modified by different metal elements. It has extremely high reaction activity and high C2+ alcohol selectivity for syngas conversion, and the CO conversion rate and C2+ alcohol selectivity on some catalysts reach more than 90% at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a graph showing the 100-hour reaction result of the Ga-modified molybdenum-based phosphorus-sulfur composite catalyst in Example 8. DETAILED DESCRIPTION

[0018] The present invention is further described below in conjunction with specific implementation cases. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Various equivalent modifications of the present invention made by those skilled in the art all fall within the scope defined by the claims attached to this application.

[0019] Example 1

[0020] 13 grams of white phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed at a molar ratio of phosphorus: sulfur = 7, phosphorus: molybdenum ion = 0.08 to obtain mixture B, wherein mixture A was a mixture of calcium nitrate and molybdenum dioxide weighed at a molar ratio of Ca ion to molybdenum ion of 2. Mixture B was then placed in a cavity formed by an inner portion of a corundum reaction tube and a high-voltage electrode, air was introduced into the reactor at a flow rate of 1500 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 11000V and a discharge frequency of 7kHz was discharged, and the reaction lasted for 280 minutes, and finally a Ca-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity was obtained.

[0021] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Ca-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 0.2 by a mass flow meter, and the volume space velocity was 14500 h -1 The reaction conditions are reaction temperature 370 degrees, reaction pressure 2.5MPa, and reaction time 21 hours.

[0022] The evaluation results are shown in the table below.

[0023] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Ca-modified molybdenum-based phosphorus-sulfur complex catalyst 21 93

[0024] Example 2

[0025] 9 grams of red phosphorus were weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to the molar ratio of phosphorus: sulfur=1, phosphorus: molybdenum ion=1 to obtain mixture B, wherein mixture A was a mixture of barium nitrate and molybdenum trioxide weighed according to the molar ratio of Ba ion to molybdenum ion of 0.8. Mixture B was then placed in a cavity formed by the inside of a ceramic reaction tube and a high-voltage electrode, oxygen was introduced into the reactor at a flow rate of 700 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 6000V and a discharge frequency of 18kHz was discharged, and the reaction was carried out for 50 minutes, and finally a Ba-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity was obtained.

[0026] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Ba-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The mass flow meter was used to control the synthesis gas hydrogen-carbon ratio (H2 / CO) to 8 and the volume space velocity to 9000 h -1 The reaction conditions are reaction temperature 220 degrees, reaction pressure 6MPa, and reaction time 11 hours.

[0027] The evaluation results are shown in the table below.

[0028] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Ba-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 31 76

[0029] Example 3

[0030] Weigh 1 gram of black phosphorus, and mix the phosphorus, sulfur powder and mixture A at a molar ratio of phosphorus: sulfur = 0.1 and phosphorus: molybdenum ion = 35 to obtain mixture B, wherein mixture A is a mixture of zinc chloride and carbonyl molybdenum weighed at a molar ratio of Zn ion to molybdenum ion of 0.01. Then, mixture B is placed in a cavity formed by a glass reaction tube and a high-voltage electrode, and hydrogen is introduced into the reactor at a flow rate of 1600 ml / min. A high-voltage power supply is used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 12000V and a discharge frequency of 1kHz is discharged, and the reaction is carried out for 300 minutes to finally obtain a Zn-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0031] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Zn-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 4.9 with a mass flow meter and a volume space velocity of 2000 h -1 The reaction conditions are reaction temperature 290 degrees, reaction pressure 9.3MPa, and reaction time 23.5 hours.

[0032] The evaluation results are shown in the table below.

[0033] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Zn-modified molybdenum-based sulfur-phosphorus complex catalyst 45 91

[0034] Example 4

[0035] Weigh 27 grams of purple phosphorus, and mix phosphorus, sulfur powder and mixture A to obtain mixture B, wherein mixture A is a mixture of potassium nitrate and ammonium molybdate weighed at a molar ratio of K ions to platinum ions of 0.05. Mixture B is then placed in a cavity formed by an inner corundum reaction tube and a high-voltage electrode, and nitrogen is introduced at a flow rate of 1400 ml / min in a reactor, and high-voltage power is used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 23000V and a discharge frequency of 6kHz is discharged, and the reaction is performed for 150 minutes to finally obtain a K-modified molybdenum-based sulfur-phosphorus complex catalyst with high C2+ alcohol selectivity.

[0036] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohol reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh K-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The mass flow meter was used to control the synthesis gas hydrogen-carbon ratio (H2 / CO) to 7 and the volume space velocity to 11500 h -1 The reaction conditions are reaction temperature 395 degrees, reaction pressure 6.5MPa, and reaction time 5 hours.

[0037] The evaluation results are shown in the table below.

[0038] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) K-modified molybdenum-based phosphorus-sulfur complex catalyst 91 93

[0039] Example 5

[0040] 12 grams of white phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed at a molar ratio of phosphorus: sulfur = 2, phosphorus: molybdenum ion = 0.35 to obtain mixture B, wherein mixture A was a mixture of sodium sulfate and molybdenum dioxide weighed at a molar ratio of Na ion to molybdenum ion of 3. Mixture B was then placed in a cavity formed by the interior of a ceramic reaction tube and a high-voltage electrode, helium was introduced into the reactor at a flow rate of 5 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 9000V and a discharge frequency of 19kHz was discharged, and the reaction was carried out for 5 minutes, and finally a Na-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity was obtained.

[0041] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Na-modified molybdenum-based sulfur-phosphorus complex catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 2.5 with a mass flow meter and a volume space velocity of 300 h -1 The reaction conditions are reaction temperature 210 degrees, reaction pressure 8.3 MPa, and reaction time 21.5 hours.

[0042] The evaluation results are shown in the table below.

[0043] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Na-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 73 87

[0044] Example 6

[0045] 6 grams of red phosphorus elemental substance was weighed, and phosphorus elemental substance, sulfur elemental substance powder and mixture A were uniformly mixed according to the molar ratio of phosphorus elemental substance: sulfur elemental substance=0.3 and phosphorus elemental substance: molybdenum ion=0.6 to obtain mixture B, wherein mixture A was a mixture of niobium nitrate and molybdenum trioxide weighed according to the molar ratio of Nb ion to molybdenum ion of 1.5. Mixture B was then placed in a cavity formed by the interior of a glass reaction tube and a high-voltage electrode, Ar was introduced into the reactor at a flow rate of 800 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 22000V and a discharge frequency of 13kHz was discharged, and the reaction was carried out for 140 minutes, and finally a Nb-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity was obtained.

[0046] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohol reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Nb-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 1.5 by a mass flow meter, and the volume space velocity was 10500h -1 The reaction conditions are reaction temperature 200 degrees, reaction pressure 11.4MPa, and reaction time 16 hours.

[0047] The evaluation results are shown in the table below.

[0048] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Nb-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 39 82

[0049] Example 7

[0050] 40 grams of black phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed at a molar ratio of phosphorus: sulfur = 3.3, phosphorus: molybdenum ion = 10 to obtain mixture B, wherein mixture A was a mixture of sodium nitrate and carbonyl molybdenum weighed at a molar ratio of Na ion to molybdenum ion of 1. Mixture B was then placed in a cavity formed by a glass reaction tube and a high-voltage electrode, air was introduced into the reactor at a flow rate of 1300 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 1000V and a discharge frequency of 20kHz was discharged, and the reaction was carried out for 160 minutes, and finally a Na-modified molybdenum-based sulfur-phosphorus complex catalyst with high C2+ alcohol selectivity was obtained.

[0051] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Na-modified molybdenum-based sulfur-phosphorus complex catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 7.5 with a mass flow meter and the volume space velocity was 9500 h -1 The reaction conditions are reaction temperature 310 degrees, reaction pressure 7MPa, and reaction time 12 hours.

[0052] The evaluation results are shown in the table below.

[0053] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Na-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 91 90

[0054] Example 8

[0055] 7 grams of purple phosphorus were weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to phosphorus: sulfur = 9, phosphorus: molybdenum ion molar ratio = 0.74 to obtain mixture B, wherein mixture A was a mixture of gallium nitrate and ammonium molybdate weighed according to Ga ion and molybdenum ion molar ratio of 0.18. Mixture B was then placed in a cavity formed by the inside of a corundum reaction tube and a high-voltage electrode, oxygen was introduced at a flow rate of 100 ml / min in the reactor, and high-voltage power was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 21000V and a discharge frequency of 14kHz was discharged, and the reaction was performed for 70 minutes to finally obtain a Ga-modified molybdenum-based sulfur-phosphorus complex catalyst with high C2+ alcohol selectivity.

[0056] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohol reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Ga-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The mass flow meter was used to control the synthesis gas hydrogen-carbon ratio (H2 / CO) to 2.3 and the volume space velocity to 6000 h -1 The reaction conditions are reaction temperature 385 degrees, reaction pressure 10.2MPa, and reaction time 22.5 hours.

[0057] The evaluation results are shown in the table below.

[0058] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Ga-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 95 96

[0059] Example 9

[0060] 37 grams of red phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed at a molar ratio of phosphorus: sulfur = 0.2 and phosphorus: molybdenum ion = 5 to obtain mixture B, wherein mixture A was a mixture of iron sulfate and molybdenum trioxide weighed at a molar ratio of Fe ion to molybdenum ion of 50. Mixture B was then placed in a cavity formed by an interior of a ceramic reaction tube and a high-voltage electrode, hydrogen was introduced into the reactor at a flow rate of 50 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, an output voltage of 13000V, and a high-voltage electricity with a discharge frequency of 3kHz was discharged, and the reaction lasted for 130 minutes, and finally a Fe-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity was obtained.

[0061] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Fe-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 5 with a mass flow meter and a volume space velocity of 10000 h -1 The reaction conditions are reaction temperature of 250 degrees, reaction pressure of 7.5 MPa, and reaction time of 15 hours.

[0062] The evaluation results are shown in the table below.

[0063] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Fe-modified molybdenum-based sulfur-phosphorus complex catalyst 76 87

[0064] Example 10

[0065] Weigh 20 grams of black phosphorus, and mix the phosphorus, sulfur powder and mixture A at a molar ratio of phosphorus: sulfur = 2.7, phosphorus: molybdenum ion = 0.1 to obtain mixture B, wherein mixture A is a mixture of zirconium nitrate and carbonyl molybdenum weighed at a molar ratio of Zr ion to molybdenum ion of 0.67. Then, mixture B is placed in a cavity formed by the inside of a glass reaction tube and a high-voltage electrode, and nitrogen is introduced into the reactor at a flow rate of 1200 ml / min. A high-voltage power supply is used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 8000V and a discharge frequency of 21kHz is discharged, and the reaction is carried out for 230 minutes, and finally a Zr-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity is obtained.

[0066] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohol reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Zr-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 3.3 and the volume space velocity was 4500 h-1 using a mass flow meter. -1 The reaction conditions are reaction temperature 375 degrees, reaction pressure 6.2MPa, and reaction time 6 hours.

[0067] The evaluation results are shown in the table below.

[0068] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Zr-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 66 93

[0069] Embodiment 11

[0070] 4 grams of purple phosphorus were weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to phosphorus: sulfur=1.5, phosphorus: molybdenum ion molar ratio=30 to obtain mixture B, wherein mixture A was a mixture of cerium nitrate and ammonium molybdate weighed according to Ce ion and molybdenum ion molar ratio of 3.5. Mixture B was then placed in a cavity formed by the inside of a corundum reaction tube and a high-voltage electrode, and He was introduced at a flow rate of 200 ml / min in a reactor, and high-voltage power was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 5500V and a discharge frequency of 8kHz was discharged, and the reaction was performed for 10 minutes to finally obtain a Ce-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0071] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Ce-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 9.5 with a mass flow meter and a volume space velocity of 400 h -1 The reaction conditions are reaction temperature 320 degrees, reaction pressure 3MPa, and reaction time 14 hours.

[0072] The evaluation results are shown in the table below.

[0073] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Ce-modified molybdenum-based sulfur-phosphorus complex catalyst 91 92

[0074] Example 12

[0075] 28 grams of white phosphorus were weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to the molar ratio of phosphorus: sulfur=6.2 and phosphorus: molybdenum ion=33.7 to obtain mixture B, wherein mixture A was a mixture of zinc chloride and molybdenum dioxide weighed according to the molar ratio of Zn ion to molybdenum ion of 0.2. Mixture B was then placed in a cavity formed by the inside of a ceramic reaction tube and a high-voltage electrode, Ar was introduced into the reactor at a flow rate of 600 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 20000V and a discharge frequency of 17kHz was discharged, and the reaction was carried out for 240 minutes to finally obtain a Zn-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0076] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Zn-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The mass flow meter was used to control the synthesis gas hydrogen-carbon ratio (H2 / CO) to 4.4 and the volume space velocity to 7000 h -1 The reaction conditions are reaction temperature 390 degrees, reaction pressure 5.1 MPa, and reaction time 20.5 hours.

[0077] The evaluation results are shown in the table below.

[0078] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Zn-modified molybdenum-based sulfur-phosphorus complex catalyst 78 80

[0079] Embodiment 13

[0080] 11 grams of red phosphorus were weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to phosphorus: sulfur=0.7, phosphorus: molybdenum ion molar ratio=2.74 to obtain mixture B, wherein mixture A was a mixture of manganese nitrate and molybdenum trioxide weighed according to the molar ratio of Mn ion to molybdenum ion of 6.3. Mixture B was then placed in a cavity formed by the interior of a glass reaction tube and a high-voltage electrode, N2 was introduced at a flow rate of 60 ml / min in a reactor, high-voltage power was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 3000V and a discharge frequency of 22kHz was discharged, and the reaction was carried out for 40 minutes to finally obtain a Mn-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0081] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Mn-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The mass flow meter was used to control the synthesis gas hydrogen-carbon ratio (H2 / CO) to 4.5 and the volume space velocity to 11000 h -1 The reaction conditions are reaction temperature 240 degrees, reaction pressure 8MPa, and reaction time 24 hours.

[0082] The evaluation results are shown in the table below.

[0083] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Mn-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 65 89

[0084] Embodiment 14

[0085] 32 grams of black phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to the molar ratio of phosphorus: sulfur = 3.5, phosphorus: molybdenum ion = 0.15 to obtain mixture B, wherein mixture A was a mixture of copper chloride and carbonyl molybdenum weighed according to the molar ratio of Cu ion to molybdenum ion of 0.05. Mixture B was then placed in a cavity formed by the inside of a corundum reaction tube and a high-voltage electrode, and He was introduced into the reactor at a flow rate of 1700 ml / min, and a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete the ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 14000V and a discharge frequency of 2kHz was discharged, and the reaction was carried out for 250 minutes, and finally a Cu-modified molybdenum-based sulfur-phosphorus complex catalyst with high C2+ alcohol selectivity was obtained.

[0086] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohol reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Cu-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled by a mass flow meter to be 9, and the volume space velocity was 7500 h -1 The reaction conditions are reaction temperature 360 ​​degrees, reaction pressure 9.7MPa, and reaction time 19.5 hours.

[0087] The evaluation results are shown in the table below.

[0088] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Cu-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 91 90

[0089] Embodiment 15

[0090] Weigh 25 grams of purple phosphorus, and mix phosphorus, sulfur powder and mixture A uniformly to obtain mixture B according to phosphorus: sulfur=8, phosphorus: molybdenum ion molar ratio=11.6, wherein mixture A is a mixture of ammonium tungstate and ammonium molybdate weighed according to W ion and molybdenum ion molar ratio of 0.55. Then, mixture B is placed in a cavity formed by the inside of a ceramic reaction tube and a high-voltage electrode, and Ar is introduced at a flow rate of 2000 ml / min in a reactor, and a high-voltage power supply is used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 19000V and a discharge frequency of 37kHz is discharged, and the reaction is performed for 80 minutes, and finally a W-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity is obtained.

[0091] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh W-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 2 by a mass flow meter, and the volume space velocity was 3000 h -1 The reaction conditions are reaction temperature 305 degrees, reaction pressure 12MPa, and reaction time 13 hours.

[0092] The evaluation results are shown in the table below.

[0093] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) W modified molybdenum-based phosphorus-sulfur complex catalyst 43 90

[0094] Example 16

[0095] 2 grams of black phosphorus were weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to the molar ratio of phosphorus: sulfur=8.3 and phosphorus: molybdenum ion=22.6 to obtain mixture B, wherein mixture A was a mixture of potassium sulfate and molybdenum trioxide weighed according to the molar ratio of K ion to molybdenum ion of 11.5. Mixture B was then placed in a cavity formed by the inside of a corundum reaction tube and a high-voltage electrode, air was introduced into the reactor at a flow rate of 850 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 2000V and a discharge frequency of 25kHz was discharged, and the reaction was carried out for 170 minutes to finally obtain a K-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0096] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh K-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The mass flow meter was used to control the synthesis gas hydrogen-carbon ratio (H2 / CO) to 6.5 and the volume space velocity to 6600 h -1 The reaction conditions are reaction temperature 330 degrees, reaction pressure 4.3MPa, and reaction time 23 hours.

[0097] The evaluation results are shown in the table below.

[0098] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) K-modified molybdenum-based phosphorus-sulfur complex catalyst 68 91

[0099] Embodiment 17

[0100] 22 grams of white phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed at a molar ratio of phosphorus: sulfur = 9.5, phosphorus: molybdenum ion = 0.5 to obtain mixture B, wherein mixture A was a mixture of sodium nitrate and carbonyl molybdenum weighed at a molar ratio of Na ion to molybdenum ion of 40. Mixture B was then placed in a cavity formed by an interior of a ceramic reaction tube and a high-voltage electrode, oxygen was introduced into the reactor at a flow rate of 900 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, an output voltage of 22500V, and a high-voltage electricity with a discharge frequency of 9kHz was discharged, and the reaction lasted for 20 minutes, and finally a Na-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity was obtained.

[0101] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Na-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 1.2 by a mass flow meter, and the volume space velocity was 12000 h -1 The reaction conditions are reaction temperature 300 degrees, reaction pressure 3.5MPa, and reaction time 9 hours.

[0102] The evaluation results are shown in the table below.

[0103] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Na-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 36 77

[0104] Embodiment 18

[0105] Weigh 29 grams of red phosphorus, and mix phosphorus, sulfur powder and mixture A at a molar ratio of phosphorus: sulfur=6, phosphorus: molybdenum ion=15.7 to obtain mixture B, wherein mixture A is a mixture of cobalt nitrate and ammonium molybdate weighed at a molar ratio of Co ion to molybdenum ion of 0.95. Then, mixture B is placed in a cavity formed by a glass reaction tube and a high-voltage electrode, and hydrogen is introduced into the reactor at a flow rate of 500 ml / min. A high-voltage power supply is used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 10000V and a discharge frequency of 27kHz is discharged, and the reaction is carried out for 260 minutes to finally obtain a Co-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0106] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Co-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 4 with a mass flow meter and a volume space velocity of 8000 h -1 The reaction conditions are reaction temperature of 350 degrees, reaction pressure of 9.6 MPa, and reaction time of 22 hours.

[0107] The evaluation results are shown in the table below.

[0108] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Co-modified molybdenum-based phosphorus-sulfur complex catalyst 56 97

[0109] Embodiment 19

[0110] 5 grams of black phosphorus were weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to the molar ratio of phosphorus: sulfur = 9.2, phosphorus: molybdenum ion = 26.6 to obtain mixture B, wherein mixture A was a mixture of rhodium chloride and molybdenum trioxide weighed according to the molar ratio of Rh ion to molybdenum ion of 9.5. Mixture B was then placed in a cavity formed by the interior of a ceramic reaction tube and a high-voltage electrode, nitrogen was introduced into the reactor at a flow rate of 70 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 15000V and a discharge frequency of 29kHz was discharged, and the reaction lasted for 90 minutes, and finally a Rh-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity was obtained.

[0111] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Rh-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 0.9 with a mass flow meter and a volume space velocity of 500 h -1 The reaction conditions are reaction temperature 335 degrees, reaction pressure 10MPa, and reaction time 18.5 hours.

[0112] The evaluation results are shown in the table below.

[0113] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Rh modified molybdenum-based phosphorus-sulfur complex catalyst 91 93

[0114] Embodiment 20

[0115] 39 grams of purple phosphorus were weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to phosphorus: sulfur=0.5, phosphorus: platinum ion molar ratio=40 to obtain mixture B, wherein mixture A was a mixture of palladium chloride and carbonyl molybdenum weighed according to the molar ratio of Pd ion to platinum ion of 10. Mixture B was then placed in a cavity formed by the interior of a glass reaction tube and a high-voltage electrode, and He was introduced at a flow rate of 300 ml / min in a reactor, and a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrodes to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 15500V and a discharge frequency of 40kHz was discharged, and the reaction was performed for 180 minutes to finally obtain a Pd-modified molybdenum-based sulfur-phosphorus complex catalyst with high C2+ alcohol selectivity.

[0116] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Pd-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 10 and the volume space velocity was 13000 h-1 using a mass flow meter. -1 The reaction conditions are reaction temperature 260 degrees, reaction pressure 4MPa, and reaction time 7 hours.

[0117] The evaluation results are shown in the table below.

[0118] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Pd-modified molybdenum-based phosphorus-sulfur complex catalyst 75 88

[0119] Embodiment 21

[0120] 14 grams of white phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to the molar ratio of phosphorus: sulfur=8.5 and phosphorus: molybdenum ion=25.85 to obtain mixture B, wherein mixture A was a mixture of cadmium nitrate and ammonium molybdate weighed according to the molar ratio of Cd ion to molybdenum ion of 19.1. Mixture B was then placed in a cavity formed by the inside of a corundum reaction tube and a high-voltage electrode, Ar was introduced at a flow rate of 40 ml / min in the reactor, and high-voltage electricity was generated at both ends of the electrode by a high-voltage power supply to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 5000V and a discharge frequency of 10kHz was discharged, and the reaction was carried out for 270 minutes to finally obtain a Cd-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0121] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Cd-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 3.5 and the volume space velocity was 3500 h-1 using a mass flow meter. -1 The reaction conditions are reaction temperature 365 degrees, reaction pressure 5.5MPa, and reaction time 17 hours.

[0122] The evaluation results are shown in the table below.

[0123] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Cd-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 54 76

[0124] Embodiment 22

[0125] 33 grams of red phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to the molar ratio of phosphorus: sulfur = 2.5, phosphorus: molybdenum ion = 0.2 to obtain mixture B, wherein mixture A was a mixture of gallium chloride and molybdenum trioxide weighed according to the molar ratio of Ga ion to molybdenum ion of 22.5. Mixture B was then placed in a cavity formed by the inside of a ceramic reaction tube and a high-voltage electrode, air was introduced into the reactor at a flow rate of 1000 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 3500V and a discharge frequency of 40kHz was discharged, and the reaction was carried out for 30 minutes to finally obtain a Ga-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0126] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Ga-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The mass flow meter was used to control the synthesis gas hydrogen-carbon ratio (H2 / CO) to 8.5 and the volume space velocity to 4000 h -1 The reaction conditions are reaction temperature 340 degrees, reaction pressure 7.7MPa, and reaction time 17.5 hours.

[0127] The evaluation results are shown in the table below.

[0128] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Ga-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 79 90

[0129] Embodiment 23

[0130] 26 grams of black phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed at a molar ratio of phosphorus: sulfur = 5, phosphorus: molybdenum ion = 35.45 to obtain mixture B, wherein mixture A was a mixture of zinc nitrate and carbonyl molybdenum weighed at a molar ratio of Zn ion to molybdenum ion of 30. Mixture B was then placed in a cavity formed by the interior of a glass reaction tube and a high-voltage electrode, oxygen was introduced into the reactor at a flow rate of 30 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 16000V and a discharge frequency of 35kHz was discharged, and the reaction lasted for 190 minutes, and finally a Zn-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity was obtained.

[0131] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Zn-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The mass flow meter was used to control the synthesis gas hydrogen-carbon ratio (H2 / CO) to 2.5 and the volume space velocity to 8500 h -1 The reaction conditions are reaction temperature 275 degrees, reaction pressure 11.5MPa, and reaction time 10 hours.

[0132] The evaluation results are shown in the table below.

[0133] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Zn-modified molybdenum-based sulfur-phosphorus complex catalyst 43 81

[0134] Embodiment 24

[0135] Weigh 3 grams of purple phosphorus, and mix phosphorus, sulfur powder and mixture A to obtain mixture B, wherein mixture A is a mixture of nickel nitrate and ammonium molybdate weighed at a molar ratio of 17.6 between Ni ions and molybdenum ions. Mixture B is then placed in a cavity formed by an inner corundum reaction tube and a high-voltage electrode, and hydrogen is introduced at a flow rate of 1100 ml / min in a reactor, and high-voltage power is used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and an output voltage of 4000V and a high-voltage electricity of a discharge frequency of 11kHz are discharged, and the reaction is performed for 100 minutes to finally obtain a Ni-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0136] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Ni-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 0.5 by a mass flow meter, and the volume space velocity was 14000 h -1 The reaction conditions are reaction temperature of 350 degrees, reaction pressure of 4.5 MPa, and reaction time of 16.5 hours.

[0137] The evaluation results are shown in the table below.

[0138]

[0139]

[0140] Embodiment 25

[0141] Weigh 30 grams of purple phosphorus, and mix phosphorus, sulfur powder and mixture A uniformly to obtain mixture B according to phosphorus: sulfur=7.5, phosphorus: platinum ion molar ratio=15, wherein mixture A is a mixture of copper sulfate and carbonyl molybdenum weighed at a Cu ion and platinum ion molar ratio of 0.5. Mixture B is then placed in a cavity formed by the interior of a ceramic reaction tube and a high-voltage electrode, and nitrogen is introduced at a flow rate of 1800 ml / min in a reactor, and a high-voltage power supply is used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and an output voltage of 24000V and a high-voltage electricity of a discharge frequency of 33kHz are discharged, and the reaction is performed for 200 minutes to finally obtain a Cu-modified molybdenum-based sulfur-phosphorus complex catalyst with high C2+ alcohol selectivity.

[0142] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohol reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Cu-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 1 with a mass flow meter and the volume space velocity was 5500 h -1 The reaction conditions are reaction temperature 275 degrees, reaction pressure 9 MPa, and reaction time 18 hours.

[0143] The evaluation results are shown in the table below.

[0144] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Cu-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 56 75

[0145] Embodiment 26

[0146] 15 grams of red phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed at a molar ratio of phosphorus: sulfur = 10, phosphorus: molybdenum ion = 20 to obtain mixture B, wherein mixture A was a mixture of nickel nitrate and ammonium molybdate weighed at a molar ratio of Ni ion to molybdenum ion of 20. Mixture B was then placed in a cavity formed by the interior of a glass reaction tube and a high-voltage electrode, He was introduced into the reactor at a flow rate of 15 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 17000V and a discharge frequency of 5kHz was discharged, and the reaction lasted for 210 minutes, and finally a Ni-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity was obtained.

[0147] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Ni-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 5.5 with a mass flow meter and a volume space velocity of 1000 h -1 The reaction conditions are reaction temperature 270 degrees, reaction pressure 10.5MPa, and reaction time 15.5 hours.

[0148] The evaluation results are shown in the table below.

[0149] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Ni-modified molybdenum-based sulfur-phosphorus complex catalyst 88 90

[0150] Embodiment 27

[0151] 8 grams of white phosphorus were weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to the molar ratio of phosphorus: sulfur=6.5 and phosphorus: molybdenum ion=27.23 to obtain mixture B, wherein mixture A was a mixture of potassium sulfate and molybdenum dioxide weighed according to the molar ratio of K ion to molybdenum ion of 23.5. Mixture B was then placed in a cavity formed by the interior of a glass reaction tube and a high-voltage electrode, air was introduced into the reactor at a flow rate of 400 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, and the high-voltage electricity with an output voltage of 25000V and a discharge frequency of 30kHz was discharged, and the reaction was carried out for 60 minutes to finally obtain a K-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0152] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh K-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 3 with a mass flow meter and a volume space velocity of 2500 h -1 The reaction conditions are reaction temperature 400 degrees, reaction pressure 5MPa, and reaction time 8 hours.

[0153] The evaluation results are shown in the table below.

[0154] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) K-modified molybdenum-based phosphorus-sulfur complex catalyst 91 92

[0155] Embodiment 28

[0156] Weigh 35 grams of red phosphorus, and mix the phosphorus, sulfur powder and mixture A at a molar ratio of phosphorus: sulfur = 4, phosphorus: molybdenum ion = 0.7 to obtain mixture B, wherein mixture A is a mixture of lead nitrate and molybdenum trioxide weighed at a molar ratio of Pb ion to molybdenum ion of 5. Then place mixture B in a cavity formed by the inside of a corundum reaction tube and a high-voltage electrode, introduce oxygen at a flow rate of 80 ml / min in the reactor, use a high-voltage power supply to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, output voltage 18000V, discharge frequency 15kHz high-voltage electricity for discharge, react for 220 minutes, and finally obtain a Pb-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0157] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Pb-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 0.7 and the volume space velocity was 15000 h-1 using a mass flow meter. -1 The reaction conditions are reaction temperature 225 degrees, reaction pressure 11MPa, and reaction time 14.5 hours.

[0158] The evaluation results are shown in the table below.

[0159] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Pb-modified molybdenum-based phosphorus-sulfur complex catalyst 57 86

[0160] Embodiment 29

[0161] 10 grams of black phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to the molar ratio of phosphorus: sulfur = 5.5, phosphorus: molybdenum ion = 11.5 to obtain mixture B, wherein mixture A was a mixture of chromium chloride and carbonyl molybdenum weighed according to the molar ratio of Cr ion to molybdenum ion of 34.5. Mixture B was then placed in a cavity formed by the inside of a ceramic reaction tube and a high-voltage electrode, hydrogen was introduced into the reactor at a flow rate of 1900 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, an output voltage of 7000V, and a high-voltage electricity with a discharge frequency of 12kHz was discharged, and the reaction was carried out for 120 minutes, and finally a Cr-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity was obtained.

[0162] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh Cr-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 6 with a mass flow meter and a volume space velocity of 5000 h -1 The reaction conditions are reaction temperature 280 degrees, reaction pressure 8.5MPa, and reaction time 20 hours.

[0163] The evaluation results are shown in the table below.

[0164] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) Cr-modified Molybdenum-based Sulfur-Phosphorus Complex Catalyst 76 70

[0165] Embodiment 30

[0166] 16 grams of purple phosphorus was weighed, and phosphorus, sulfur powder and mixture A were uniformly mixed according to the molar ratio of phosphorus: sulfur=3, phosphorus: molybdenum ion=25 to obtain mixture B, wherein mixture A was a mixture of lanthanum nitrate and ammonium molybdate weighed according to the molar ratio of La ion to molybdenum ion of 4. Mixture B was then placed in a cavity formed by the inside of a glass reaction tube and a high-voltage electrode, nitrogen was introduced into the reactor at a flow rate of 90 ml / min, a high-voltage power supply was used to generate high-voltage electricity at both ends of the electrode to complete ionization of the gas to form plasma, an output voltage of 8500V, and a high-voltage electricity with a discharge frequency of 16kHz was discharged, and the reaction was carried out for 110 minutes to finally obtain a La-modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity.

[0167] The catalytic performance of the above-synthesized catalyst in the synthesis gas to C2+ alcohols reaction was evaluated as follows: First, 1.5 mL of 40-60 mesh La-modified molybdenum-based sulfur-phosphorus composite catalyst was evenly mixed with quartz sand and loaded into a high-pressure fixed bed reactor. The synthesis gas hydrogen-carbon ratio (H2 / CO) was controlled to be 1.75 with a mass flow meter and a volume space velocity of 1500 h -1 The reaction conditions are reaction temperature 380 degrees, reaction pressure 9.5MPa, and reaction time 19 hours.

[0168] The evaluation results are shown in the table below.

[0169] catalyst CO conversion rate (%) C2+ alcohol selectivity (%) La-modified Mo-based Sulfur-Phosphorus Complex Catalyst 93 92

[0170] The embodiments of the present invention are only for illustrating the present invention and are not intended to limit the present invention.

Claims

1. A method for synthesizing a metal element modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity, characterized in that: Follow the steps below Step 1, preparing a mixture A, mixing the modified metal salt and the molybdenum compound uniformly to obtain a mixture A, wherein the molar ratio of the modified metal to molybdenum in the mixture A is 0.01-50; Step 2, preparing a mixture B, mixing phosphorus powder, sulfur powder and mixture A uniformly to obtain a mixture B, wherein the molar ratio of phosphorus to sulfur is 0.1-10, and the molar ratio of phosphorus to molybdenum is 0.05-40; Step 3: Place the mixture B in a reaction tube of a plasma reactor, introduce discharge gas at a flow rate of 5-2000 ml / min, output voltage of 1000-25000 V, and discharge frequency of 1-40 kHz to ionize the gas to form plasma, react for 5-300 minutes, and finally obtain a metal element modified molybdenum-based sulfur-phosphorus complex catalyst with high C2+ alcohol selectivity.

2. The method for synthesizing a metal element modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity according to claim 1, characterized in that: The modified metal salt is one of nickel sulfate, nickel nitrate, nickel chloride, sodium sulfate, sodium nitrate, sodium chloride, calcium sulfate, calcium nitrate, calcium chloride, barium sulfate, barium nitrate, barium chloride, niobium sulfate, niobium nitrate, niobium chloride, rhodium sulfate, rhodium nitrate, rhodium chloride, palladium sulfate, palladium nitrate, palladium chloride, platinum sulfate, platinum nitrate, platinum chloride, cadmium sulfate, cadmium nitrate, cadmium chloride, gallium sulfate, gallium nitrate, gallium chloride, lanthanum sulfate, lanthanum nitrate, lanthanum chloride, zirconium sulfate, zirconium nitrate, zirconium chloride, cerium sulfate, cerium nitrate, cerium chloride, zinc sulfate, zinc nitrate, zinc chloride, manganese sulfate, manganese nitrate, manganese chloride, copper sulfate, copper nitrate, copper chloride, ferric sulfate, ferric nitrate, ferric chloride, chromium sulfate, chromium nitrate, chromium chloride, ammonium tungstate, potassium sulfate, potassium nitrate or potassium chloride.

3. The method for synthesizing a metal element modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity according to claim 1, characterized in that: The molybdenum compound is one of carbonyl molybdenum, ammonium molybdate, molybdenum dioxide or molybdenum trioxide.

4. The method for synthesizing a metal element modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity according to claim 1, characterized in that: The phosphorus element is one of white phosphorus, red phosphorus, black phosphorus or purple phosphorus.

5. The method for synthesizing a metal element modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity according to claim 1, characterized in that: The reaction tube is one of a corundum tube, a glass tube or a ceramic tube.

6. The method for synthesizing a metal element modified molybdenum-based sulfur-phosphorus composite catalyst with high C2+ alcohol selectivity according to claim 1, characterized in that: The discharge gas is one of air, oxygen, H2, N2, He or Ar.

7. An application of a metal element modified molybdenum-based sulfur-phosphorus composite catalyst prepared by the synthesis method described in any one of claims 1 to 6, characterized in that: The 40-60 mesh metal element modified molybdenum-based sulfur-phosphorus composite catalyst was uniformly mixed with quartz sand and loaded into a high-temperature and high-pressure fixed-bed reactor. The hydrogen-carbon ratio of the synthesis gas was controlled to be 0.2-10 and the volume space velocity was 300-15000 h-1. -1 The reaction conditions are reaction temperature 200-400 degrees, reaction pressure 2.5-12 MPa, and reaction time 5-24 hours.